A voz afrodescendente quilombola: cultura, identidade e ethos discursivo como imagem de si - Mezadri, Jéssica Fernanda (2017)
The history of the black in Brazil is a scene of intense struggles for social recognition, since, after one hundred years of the abolition of slavery in the country, the 1988 Constitution guaranteed the possession of lands to the remaining quilombolas. However, that was not enough. Black rural communities fought for aspects of black ancestry, historical trajectory, resistance to oppression, worship and customs. Consequently, the movements in search of social visibility have become more pronounced throughout the Brazilian territory, opening space also for scientific research. Thus, in order to collaborate with the blacks, to construct and to add new knowledge on Afrodescendants, the community Quilombola Corrêa, formed by remnants, is located in the District of São Paulo das Tunas, in the city of Giruá, in the northwest region of the state of Rio Grande The objective of this study was to analyze the discourse of cultural identity of the Community, for the construction of identity and ethos as an image of itself. It is important to understand which cultural traits are inscribed in the enunciation scene: the scenography and the ethos of this group, based on the theoreticalmethodological assumptions of the global semantics proposed by Maingueneau (2008a, 2008b, 2012). The construction of the scenography and the discursive ethos of the remnants of the Quilombola Corrêa Redoubt on the self-image, as well as the investigation of how the global semantics was constituted - that scenography and ethos discourses were constructed. Similarly, we sought to understand the identity constitution of quilombolas with their cultural universe, based on the theoretical contributions of authors such as Hall (2015), Woodward (2014) and Bhabha (2001), as an interaction between pre-discursive and The discursive ethos in the construction of the quilombo identity from the oral reports of these. The research is exploratory and descriptive regarding its objectives, it is a field research involving bibliographic procedures with qualitative approach. The corpus of this research was the discourse of the residents of the Quilombola Corrêa Community, collected in a focal group. It was found that the remnants know little about their own history as a quilombo, making utopian recognition, since in their discourses there is the construction of ethos that are demanding and discontent with the current one of survival. These "morenos" affirm to be accepted, but they enunciate several aspects of social invisibility. Many of these quilombolas feel obliged to praise the white man who gave him employment and housing, without realizing hegemony, oppression and the forces of power.